Oocytes Selected Using BCB Staining Enhance Nuclear Reprogramming and the In Vivo Development of SCNT Embryos in Cattle - Su, Jianmin; Wang, Yongsheng; Li, Ruizhe; Peng, Hui; Hua, Song; Li, Qian; Quan, Fusheng; Guo, Zekun; Zhang, Yong (PLOS ONE, 2012)
The selection of good quality oocytes is crucial for in vitro fertilization and somatic cloning. Brilliant cresyl blue (BCB) staining has been used for selection of oocytes from several mammalian species. However, the effects of differential oocyte selection by BCB staining on nuclear reprogramming and in vivo development of SCNT embryos are not well understood. Immature compact cumulus–oocyte complexes (COCs) were divided into control (not exposed to BCB), BCB+ (blue cytoplasm) and BCB− (colorless cytoplasm) groups. We found that BCB+ oocytes yielded a significantly higher somatic cell nuclear transfer (SCNT) blastocyst rate and full term development rate of bovine SCNT embryos than the BCB− and control oocytes. BCB+ embryos (embryos developed from BCB+ oocytes) showed increased acetylation levels of histone H3 at K9 and K18 (AcH3K9, AcH3K18), and methylation levels of histone H3 at K4 (H3K4me2) than BCB− embryos (embryos developed from BCB− oocytes) at the two-cell stage. Furthermore, BCB+ embryos generated more total cells, trophectoderm (TE) cells, and inner cell mass (ICM) cells, and fewer apoptotic cells than BCB− embryos. The expression of SOX2, CDX2, and anti-apoptotic microRNA-21 were up-regulated in the BCB+ blastocysts compared with BCB− blastocysts, whereas the expression of pro-apoptotic gene Bax was down-regulated in BCB+ blastocysts. These results strongly suggest that BCB+ oocytes have a higher nuclear reprogramming capacity, and that BCB staining can be used to select developmentally competent oocytes for nuclear transfer.